DIVERSITY OF ANTITUSSIVE PLANTS IN PURWOREJO REGENCY, CENTRAL JAVA PROVINCE - Slamet Mardiyanto Rahayu; Wahyu Aprilyaningsih (Nusantara Hasana Journal, 2026)
Purworejo is one of the regencies in Central Java Province that has biodiversity, including plants. This study aims to identify the diversity of plants that have potential as antitussive (cough-suppressing) agents in Purworejo Regency. The research was conducted using observation and identification methods, followed by a literature review to determine the potential of the plant species found as antitussives. Based on the study, there are 10 plant species that have potential as antitussives, namely: Zingiber officinale (ginger), Kaempferia galanga (kencur), Curcuma longa (turmeric), Curcuma xanthorrhiza (temulawak), Alpinia galanga (galangal), Piper betle (betel leaf), Citrus aurantiifolia (lime), Citrus hystrix (kaffir lime), Ocimum sanctum (holy basil), and Orthosiphon aristatus (cat’s whiskers).